Change in Diagnosis of Helicobacter pylori Infection in the Treatment-Failure Era - Rocco Spagnuolo; Giuseppe Guido Maria Scarlata; Maria Rosaria Paravati; Ludovico Abenavoli; Francesco Luzza (MDPI AG, 2024)
Helicobacter pylori (H. pylori) infection is a prevalent global health issue, associated with several gastrointestinal disorders, including gastritis, peptic ulcers, and gastric cancer. The landscape of H. pylori treatment has evolved over the years, with increasing challenges due to antibiotic resistance and treatment failure. Traditional diagnostic methods, such as the urea breath test, stool antigen test, and endoscopy with biopsy, are commonly used in clinical practice. However, the emergence of antibiotic-resistant strains has led to a decline in treatment efficacy, necessitating a re-evaluation of common diagnostic tools. This narrative review aims to explore the possible changes in the diagnostic approach of H. pylori infection in the era of treatment failure. Molecular techniques, including polymerase chain reaction and whole genome sequencing, which have high sensitivity and specificity, allow the detection of genes associated with antibiotic resistance. On the other hand, culture isolation and a phenotypic antibiogram could be used in the diagnostic routine, although H. pylori is a fastidious bacterium. However, new molecular approaches are promising tools for detecting the pathogen and its resistance genes. In this regard, more real-life studies are needed to reveal new diagnostic tools suitable for identifying multidrug-resistant H. pylori strains and for outlining proper treatment.